Dynamic approach and cost analysis for optimum insulation thicknesses of the building external walls - Özel, Meral (My University, 2008)
The optimum thickness of insulation applying on external walls of building was investigated under dynamic thermal conditions. Therefore, the yearly heating transmission load was calculated by using an implicit finite differences method under steady periodic conditions. Calculations were done by considering external environment conditions of Elazi? city. Extruded polystyrene was used as the insulation material, and coal, fuel-oil and natural gas were used as fuel. Then, cost analysis was done for a south facing wall insulated on outside. The optimum insulation thicknesses, the energy savings and payback periods were calculated for every fuel type. As result, optimum insulation thickness for Elazi? was obtained to be 0.040 m when natural gas was used.
Bi?na diş duvarlarinin opti?mum yalitim kalinliklari i?çi?n di?nami?k yaklaşim ve mali?yet anali?zi?
Keywords: Building wall; Cost analysis; Insulation thickness; Yearly heating load